Impulsive Buying Among Youth : A Dominating Component of Compulsive Buying Behavior - Tomar, Rohit Singh; Tomar, Deepika; Tomar, Vivek Singh (Indian Journal of Marketing, 2023)
Purpose: Impulsive buying is an outcome of external stimuli, whereas compulsive buying is a response to negative internal feelings, and jointly, they constitute compulsive buying behavior (CBB). The current study was conducted to find the dominant component of compulsive buying among youth. Design/Methodology/Approach: The Richmond Scale applied for data collection was found to discriminate between compulsive buying behavior and normal buying behavior. CBB was found in 169 of 469 youngsters (college students). SPSS 26.0 was used to do automatic regression to determine the best predictor of CBB among kids. Findings: The study discovered that buying undesirable and unplanned items were the best predictor of compulsive shopping behavior. Overall, impulsive behavior predicted compulsive buying behavior more strongly among young people. However, there was no variation in the compulsive buying scores among youth with CBB based on age or gender. Implications: As CBB is largely present among youth and is mainly triggered by impulsive buying tendencies, policymakers should formulate policies to curb the promotion of harmful products at the point of purchase. Originality Value: The current study focused on the compulsive purchasing habits of developing country youngsters. Its novelty resided in the results, which imply that impulsive purchasing is a significant component of compulsive purchasing behavior.